Menopausal Transition and Chronic Diseases - Luoto, Riitta (Current Women's Health Reviews, 2006)
Menopausal transition modifies the prevalence, incidence and timing of many chronic diseases, such as cardiovascular diseases, depression or musculoskeletal disorders. Women with early menopause, before age 45 years, have increased cardiovascular disease morbidity. This is due to interactions between menopausal transition and family history, lifestyle and socioeconomic factors. The aim of this review is to update current knowledge concerning menopausal transition and prevalence and prevention of chronic diseases, such as cardiovascular disease and mental health disorders, especially depression. Longitudinal cohort studies are the main references of the review. In conclusion, the role of early menopause in chronic disease prevention may be larger than earlier expected. Chronic disease prevention through lifestyle changes (especially increase of physical activity) is a useful tool around menopausal transition.
Keywords: lifestyle